Results of surgical therapy of functioning pituitary adenomas - Novak, Vlastimil; Hrabalek, Lumir; Schovanek, Jan; Frysak, Zdenek; Ijisesan Perryova, Racheal Temitope; Pohlodek, Daniel (Biomedical papers, 2025)
Introduction. Functioning pituitary adenomas lead to substantial morbidity and increased mortality associated with typical endocrine syndromes. Surgical therapy is an integral part of the management of these tumours. The aim of this study was to evaluate the results of surgical transnasal procedures in patients with functioning pituitary adenomas who underwent the surgery at the Department of Neurosurgery, University Hospital Olomouc. Methods. Patients with functioning pituitary adenoma (ACTH, GH, PRL) were indicated for surgery. All patients underwent preoperative and postoperative endocrinological examination and laboratory tests to assess excessive or deficient hormonal production and imaging examination. Results. The cohort consisted of 58 patients, 33 of whom were women and 25 men. The age range was 12-77 years (mean age 47.6 years). Microadenoma was diagnosed in 58.6% of patients and macroadenoma in 41.4% of patients. The most common hypersecretory syndrome was excessive production of growth hormone (56.9%), followed by excessive production of adrenocorticotropic hormone (24.1%) and prolactin (12.1%). In the group with excessive production of ACTH, complete remission was achieved after the first surgery in 78.6% of cases (72.8% for microadenomas (8) and 100% (3) cases in macroadenomas); in the group with excessive GH production in 51.4% (63.2% (7) in microadenomas and 46.2% (12) cases in macroadenomas). In the group with excessive production of PRL, it was 57.1% (100% (2) in microadenomas and 40% (2) cases in macroadenomas). Conclusion. Surgical therapy in the presented cohort led to the normalisation of hormonal excessive production in 58.6% of cases. A combination of drug therapy and radiotherapeutic methods was necessary in the remaining cases to achieve hormonal remission.
Keywords: hormone-secreting pituitary adenomas; transsphenoidal surgery; Acromegaly; Cushing's disease